2009
DOI: 10.1111/j.1365-2966.2009.15208.x
|View full text |Cite
|
Sign up to set email alerts
|

On the incidence of magnetic fields in slowly pulsating B, β Cephei and B-type emission-line stars

Abstract: We have obtained 40 high-resolution circular spectropolarimetric measurements of 12 slowly pulsating B (SPB) stars, eight β Cephei stars and two Be stars with the Echelle Spectropolarimetric Device for the Observation of Stars at CFHT (ESPaDOnS) and Narval spectropolarimeters. The aim of these observations is to evaluate recent claims of a high incidence of magnetic field detections in stars of these types obtained using low-resolution spectropolarimetry by Hubrig et al. The precision achieved is generally com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
90
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(102 citation statements)
references
References 28 publications
9
90
2
1
Order By: Relevance
“…β Cep itself was the first β Cephei star for which a Zeeman signature had been directly detected (Henrichs et al 2000). Since then, signatures have been reported for ξ 1 CMa (Hubrig et al 2006;Silvester et al 2009;FourtuneRavard et al 2011), 16 Peg (Henrichs et al 2009, and σ Lup (Henrichs et al 2011). Other magnetic β Cep stars have been suggested (e.g.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…β Cep itself was the first β Cephei star for which a Zeeman signature had been directly detected (Henrichs et al 2000). Since then, signatures have been reported for ξ 1 CMa (Hubrig et al 2006;Silvester et al 2009;FourtuneRavard et al 2011), 16 Peg (Henrichs et al 2009, and σ Lup (Henrichs et al 2011). Other magnetic β Cep stars have been suggested (e.g.…”
Section: Discussionmentioning
confidence: 95%
“…Hubrig et al 2009) but additional observations at higher signal-to-noise and resolution rejected those possible detections (e.g. Silvester et al 2009;Shultz et al 2011). In the same way, the detection of a magnetic field in the β Cephei star γ Peg claimed by Butkovskaya & Plachinda (2007) has been found to be spurious by the MiMeS collaboration (Neiner et al, in prep.).…”
Section: Discussionmentioning
confidence: 99%
“…From the observed v rot sin i = 15 ± 2 km s −1 (NP12) we can reject the second solution of Aerts et al (2006) and conclude that the star is seen equator-on, with a rotational period of about 22 d (employing R from Table 1). Hubrig et al (2009) reported the detection of a magnetic field for this object based on spectropolarimetric observations with Fors1 on the VLT, which could not be confirmed by Bagnulo et al (2012) by reanalysis of the same observational data, and also by Silvester et al (2009) based on spectropolarimetry at high spectral resolution. The origin of the mixing of the surface with CN-cycled material is compatible with evolution models accounting for the effects of rotation.…”
Section: #16: Hd 216916 (En Lac)mentioning
confidence: 99%
“…Fields have recently been discovered in a variety of types of stars such as Of?p stars (Grunhut & Wade 2012, and references therein), β Cep and slowly pulsating B stars (Henrichs et al 2000;Neiner et al 2003;Silvester et al 2009), Herbig AeBe stars (Wade et al 2005(Wade et al , 2007Catala et al 2007;Alecian et al 2013), red giant (Aurière et al 2009) and AGB supergiant stars (Grunhut et al 2010), and many kinds of cool dwarfs (Donati & Landstreet 2009, and references therein). Fields in such stars have become detectable as a result of having new generation instrumentation of very high efficiency and broad wavelength coverage available on medium and large telescopes, and through advanced data reduction and treatment techniques that allow very small polarimetric signatures to be reliably detected.…”
Section: Introductionmentioning
confidence: 99%